2021
DOI: 10.3389/fnmol.2021.665800
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Voluntary Running Wheel Exercise-Induced Extracellular Vesicles on Anxiety

Abstract: Anxiety disorders are the most frequently diagnosed psychological condition, associated with serious comorbidities including excessive fear and interference with daily life. Drugs for anxiety disorders are typically prescribed but the side effects include weight gain, nausea, and sleepiness. Exercise is an effective treatment for anxiety. Exercise induces the release of extracellular vesicles (EVs) into the circulation, which transmit signals between organs. However, the effects of exercise-induced EVs on anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
1
3
0
Order By: Relevance
“…Although the EV levels were increased in some animals, the mean EV concentration and size were not significantly different in the Pre-RUN and Post-RUN plasma samples. These results are in line with several other studies finding no significant changes in the EV concentration after the exercise ( Lovett et al, 2018 ; Hou et al, 2019 ; Yoon et al, 2021 ). This controversy suggests that different types, intensity and duration of exercise may affect the kinetics of EV release from various cell types or their clearance from the circulation in different ways.…”
Section: Discussionsupporting
confidence: 93%
“…Although the EV levels were increased in some animals, the mean EV concentration and size were not significantly different in the Pre-RUN and Post-RUN plasma samples. These results are in line with several other studies finding no significant changes in the EV concentration after the exercise ( Lovett et al, 2018 ; Hou et al, 2019 ; Yoon et al, 2021 ). This controversy suggests that different types, intensity and duration of exercise may affect the kinetics of EV release from various cell types or their clearance from the circulation in different ways.…”
Section: Discussionsupporting
confidence: 93%
“…We have previously shown that extracellular particles (EP) isolated following acute contractile activity increased cell count but not viability in myoblasts, but that study was done with a different exercise regimen, isolation method, and treatment protocol [42]. Another study reported that chronic exercise-derived EVs increased cell viability in Neuro2A cells, a mouse neuroblastoma cell line, also using different exercise regimen and protocols [71]. Interestingly, EV-depleted media treatment reduced cell count compared to conditioned media and CCA-EV treated cells, illustrating the EVdependent nature of these adaptations, and in concordance with previous work [42].…”
Section: Discussionmentioning
confidence: 99%
“…Since exercise modifies the urinary proteome (Kohler et al 2015 ) and EV miRNA profile in plasma (Yoon et al 2021 ), and both urine and urinary EVs comprise the plasma proteome (Dear et al 2013 ; Harpole et al 2016 ), we hypothesized that exercise could change the urinary EV miRNA contents. After 20 m SRT and 1 h of rest, a total of 9 miRNAs in urinary EVs were found to be altered.…”
Section: Discussionmentioning
confidence: 99%